Measuring customer satisfaction of SiteOne Landscape Supply in Dallas/Fort Worth, Texas - Montoya Nunez, Claudia (Kansas State University, 2016)
SiteOne Landscape Supply is the largest distributor of lawn care products for professionals of the landscape industry in U.S.A. and Canada. SiteOne is aware of the importance of customer satisfaction and it is interested on increasing satisfaction by improving customer service. There is a high concentration of Latino landscapers in Texas, whom customer service needs may differ from non-Latino customers. Therefore the purpose of this project was to study customer satisfaction of Hispanic and non-Hispanic landscapers considering the following thirteen service attributes: competitive prices, available stock, cleanliness of facilities, business follow up, timely assistance, timely deliveries, accuracy of orders, helpful staff, approachable staff, knowledgeable staff, Spanish-speaking staff, training in Spanish, and labels in Spanish. The data was collected throughout a survey which was presented to SiteOne customers in the Dallas/Fort Worth area. A total of 224 surveys were collected. The methods used to analyze the data were importance-performance (I-P) and regression analyses. The major differences found in the I-P grids are related to the three Spanish language attributes. Spanish-speaking staff, training in Spanish and labels in Spanish are statistically significant more important to Hispanic than non-Hispanic landscapers. Available stock is the most important attribute for non-Hispanic, and it is the second most important for Hispanic customers. SiteOne has an opportunity to improve their stock availability, especially for nursery, fertilizers and pesticides. Other factors that are very important to customers and they perceive that SiteOne is doing an excellent job are: timely assistance, timely deliveries, accuracy of orders, and approachable, knowledgeable and helpful staff. The importance of competitive prices was rated as high as the previous six service attributes, however the mean of pricing performance was not as high as that group of attributes. From the multivariate regression analyses, it was found that pricing was the only variable with statistical significance to predict changes in customer satisfaction for the non-Hispanic group. No statistical significance was found in the regression model run for Hispanic clients. Some negative coefficients with statistical significance were found for stores #199 and #220 in the models run to analyze branch performance. It is recommended that these results be compared with other measurements to determine the nature of the issues that may be present in these locations.
Keywords: Customer satisfaction; Customer service; Landscape industry